Surface-modified sulfide electrolyte as well as preparation method and application thereof
By forming a lithium -containing lithium -containing compound and halogen -containing compounds on the surface of vulcosine electrolytes, the problem of poor surface damage and electrochemical compatibility after refining sulfide electrolytes is solved, and the performance of all -solid -state batteries is improved.
Patent Information
- Application Number
- CN202411352566.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-21
AI Technical Summary
The surface damage of the existing sulfide electrolyte during the refining process leads to a decrease in ionic conductivity, narrow electrochemical window, and poor electrochemical compatibility with the positive electrode material, resulting in poor comprehensive electrochemical performance of all-solid-state batteries.
The front -wheel drive body is used to form an oxygen -containing lithium compound and halogen -containing compounds. The surface of the electrolytes after mechanical mixing and refined sulfide is evenly scattered to form a cover layer. Surface modification layer.
The surface damage of the vulcanization electrolyte is repaired, the ionic conductivity is improved, the interface impedance between the electrolyte and the positive electrode material is reduced, and the comprehensive electrochemical performance of the omnidirectional battery is enhanced.
Smart Images

Figure CN119340459A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a surface-modified sulfide electrolyte and a preparation method and application thereof. Background Art
[0002] With the rapid popularization of electric vehicle applications, lithium-ion batteries, as one of the most efficient and portable energy storage systems, have attracted great attention. However, the energy density of liquid lithium-ion batteries has almost reached its limit, and there are safety issues with the use of organic liquid electrolytes. Using solid electrolytes instead of traditional liquid electrolytes can improve the safety performance and energy of batteries. At present, the main solid electrolytes studied include polymers, oxides, halides and sulfides. Among them, sulfide electrolytes have good mechanical properties and high ionic conductivity, and are considered to be one of the most promising electrolyte materials.
[0003] The synthesis of sulfide electrolytes usually requires sintering at a relatively high temperature, resulting in a larger electrolyte particle size D50 ≥ 20 μm. Currently, the positive electrode active material D50 ≤ 15 μm. Larger electrolytes will lead to poor contact between electrode materials and high porosity. Reducing the particle size of sulfide electrolytes is crucial for the preparation of all-solid-state batteries. However, the refinement process will cause damage to the electrolyte surface, causing a significant decrease in the ionic conductivity of the electrolyte. In addition, the refined sulfide electrolyte has a narrow electrochemical window and poor electrochemical compatibility with the active material. In order to solve the interface problem between the sulfide electrolyte and the active material, the sulfide electrolyte is usually doped or coated. However, existing modification methods often lead to a decrease in the ionic conductivity of the electrolyte, and the preparation process is complex and costly.
[0004] Therefore, it is necessary to develop a surface-modified sulfide electrolyte and its preparation method and application to overcome the above difficulties. Summary of the invention
[0005] The present application aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present application proposes a surface-modified sulfide electrolyte and a preparation method and application thereof.
[0006] The first aspect of the present application provides a surface-modified sulfide electrolyte, in which a surface modification layer is formed on the surface of the refined sulfide electrolyte, and the surface modification layer can repair the surface damage of the sulfide electrolyte, and the surface modification layer has a high ionic conductivity and will not affect the ionic conductivity of the sulfide electrolyte. At the same time, it can also avoid direct contact between the sulfide electrolyte and the positive electrode material, reduce the space charge effect, and then achieve the improvement of the comprehensive electrochemical performance of the all-solid-state battery.
[0007] Specifically, a surface-modified sulfide electrolyte comprises: a sulfide electrolyte and a surface modification layer, wherein the surface modification layer is formed on the surface of the sulfide electrolyte, and the surface modification layer comprises a compound; the chemical formula of the compound is LiM a OX b , wherein 0≤a≤1, 2≤b≤4, and X is one or more of Cl, Br, and F; wherein the M element is one or more of Al, Nb, Ta, and Zr;
[0008] The compound, such as LiNb 0.6 Zr 0.4 OCl 3.6 、LiTa 0.9 Zr 0.05 Al 0.05 OCl 3.85 、LiTa 0.8 Zr 0.2 OCl 3.8 .
[0009] Preferably, the material of the surface modification layer has diffraction peaks at 2θ=14°±0.5° and 24.5°±0.5° in the X-ray diffraction spectrum.
[0010] Preferably, the chemical formula of the sulfide electrolyte is Li 7-a PS 6-a X a , wherein X is one or more of F, Cl, Br, I, 0≤a≤2, and ionic conductivity>2.0mS / cm;
[0011] The sulfide electrolytes such as Li6PS5Cl, Li 5.5 PS 4.6 Cl 1.5 , Li 5.4 PS 4.4 Cl 1.6 .
[0012] Preferably, the particle size D50 of the sulfide electrolyte is ≤8 μm, such as the particle size D50 is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm.
[0013] The second aspect of the present application provides a method for preparing a surface-modified sulfide electrolyte, which can not only repair the surface damage of the refined sulfide electrolyte, but also reduce the side reactions between the sulfide electrolyte and the positive electrode material during the cycle, reduce the solid-solid interface contact impedance, and help improve the comprehensive electrochemical performance of the all-solid-state battery.
[0014] Specifically, a method for preparing a surface-modified sulfide electrolyte comprises the following steps:
[0015] Step (1): mixing an oxygen-containing lithium compound and a halogen-containing compound to obtain a precursor;
[0016] Step (2): adding the precursor into the sulfide electrolyte and mixing them so that the oxygen-containing lithium compound and the halogen-containing compound are uniformly dispersed on the surface of the sulfide electrolyte to form a coating layer;
[0017] Step (3): subjecting the sulfide electrolyte having the coating layer to low temperature annealing treatment to obtain a sulfide electrolyte having a surface modification layer.
[0018] Preferably, the total mass of the oxygen-containing lithium compound and the halogen-containing compound is 0.1-10% of the sulfide electrolyte, such as 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10%.
[0019] Preferably, in step (1), the halogen-containing compound is one or more of NbF5, TaF5, ZrF4, AlF3, NbCl5, TaCl5, ZrCl4, AlCl3, NbBr5, TaBr5, ZrBr4, AlBr3, NbI5, TaI5, ZrI4, and AlI3; and the oxygen-containing lithium compound is one or more of Li2CO3, Li2O, and LiOH.
[0020] Preferably, in step (1), the oxygen-containing lithium compound and the halogen-containing compound are mixed by grinding.
[0021] Preferably, the grinding method is ball milling, and the rotation speed of the ball mill is 100 to 800 rpm, such as 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm;
[0022] The ball milling time is 1 to 40 hours, such as 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h.
[0023] Preferably, in step (3), the annealing temperature is 70-350°C, such as 70°C, 100°C, 150°C, 200°C, 250°C, 300°C;
[0024] The annealing time is 1 to 8 hours, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h.
[0025] Preferably, step (3) is carried out under an inert atmosphere (eg, nitrogen, argon).
[0026] A third aspect of the present application provides an application of a surface-modified sulfide electrolyte.
[0027] Specifically, an all-solid-state battery comprises a positive electrode layer, a negative electrode layer and an electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer is a composite positive electrode, and the electrolyte used for the composite positive electrode is the surface-modified sulfide electrolyte or the surface-modified sulfide electrolyte obtained by the preparation method.
[0028] Compared with the prior art, the beneficial effects of this application are as follows:
[0029] (1) The surface-modified sulfide electrolyte of the present application comprises a refined sulfide electrolyte and a surface modification layer formed on the surface of the sulfide electrolyte, wherein the surface modification layer comprises a compound having a chemical formula of LiM a OX b , wherein 0≤a≤1, 2≤b≤4, X is one or more of Cl, Br, and F, and M is one or more of Al, Nb, Ta, and Zr; surface coating of the refined sulfide electrolyte with a compound containing a specific element can repair surface damage of the sulfide electrolyte without affecting the ion transport of the sulfide electrolyte, and can also inhibit side reactions of the sulfide electrolyte and the cathode material under high voltage, reduce interfacial impedance, and improve the comprehensive electrochemical performance of the all-solid-state battery.
[0030] (2) The preparation method of the present application comprises mechanically mixing an oxygen-containing lithium compound and a halogen-containing compound to form a precursor, adding the formed precursor to a refined sulfide electrolyte, and mixing them thoroughly so that the oxygen-containing lithium compound and the halogen-containing compound are uniformly dispersed on the surface of the refined sulfide electrolyte to form a coating layer, and then performing a low-temperature annealing treatment to repair the surface damage of the refined sulfide electrolyte while forming a surface modification layer having high ionic conductivity and resistance to high voltage. The method has a simple process flow and is conducive to large-scale application. The formed surface modification layer does not reduce the ionic conductivity of the sulfide electrolyte, and also effectively avoids direct contact between the sulfide electrolyte and the positive electrode material, which can eliminate the space charge between the sulfide electrolyte and the positive electrode material, reduce the interface impedance, and reduce the side reaction between the sulfide electrolyte and the positive electrode material, thereby alleviating the failure of the sulfide electrolyte under high voltage and improving the stability of the sulfide electrolyte under high voltage, thereby achieving the improvement of the electrochemical performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the process for preparing the surface-modified sulfide electrolyte in the embodiments of the present application;
[0032] Figure 2XRD spectra of the corresponding materials in Example 1 and Comparative Example 1 of the present application;
[0033] Figure 3 The electrochemical impedance spectroscopy (EIS) diagrams of the corresponding materials in Example 2 and Comparative Example 2 of the present application are shown. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0035] It should be noted that the illustrations provided in this embodiment only illustrate the basic concept of the present application in a schematic manner, and therefore the drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0036] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which this application can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by this application, should still fall within the scope of the technical contents disclosed in this application.
[0037] The directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "middle", "longitudinal", "lateral", "horizontal", "inner", "outer", "radial", "circumferential" and the like in this specification are based on the directions or positional relationships shown in the drawings and are only for the convenience of simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operate in a specific direction, and therefore cannot be understood as limiting the present application. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0038] Example 1
[0039] The present embodiment provides a surface-modified sulfide electrolyte, in which a surface modification layer is formed on the surface of the refined sulfide electrolyte. The surface modification layer can not only repair the surface damage of the sulfide electrolyte, but also has a high ionic conductivity, will not affect the ionic conductivity of the sulfide electrolyte, and can also avoid direct contact between the sulfide electrolyte and the positive electrode material, thereby reducing the space charge effect.
[0040] Please refer to Figure 1As shown, the preparation method of the surface-modified sulfide electrolyte comprises the following steps:
[0041] S201, weigh 0.67 g NbCl5, 0.38 g ZrCl4, and 0.099 g LiOH, and then grind the above raw materials in proportion by ball milling at 650 rpm for 10 h to obtain a precursor;
[0042] S202, adding the above-obtained precursor to 10 g of refined sulfide electrolyte Li6PS5Cl (D50 is 3 μm), and then ball milling at 200 rpm for 2 h to uniformly disperse the precursor on the surface of the sulfide electrolyte to form a coating layer;
[0043] S203, the sulfide electrolyte with the coating layer is transferred to a tube furnace and sintered in an argon atmosphere at a temperature of 120°C for 2 hours, and then a surface modification layer with high ionic conductivity and high voltage resistance is formed on the surface of the refined sulfide electrolyte, that is, a sulfide electrolyte Li6PS5Cl@LiNb with a surface modification layer is obtained. 0.6 Zr 0.4 OCl 3.6 .
[0044] Example 2
[0045] The present embodiment provides a surface-modified sulfide electrolyte, in which a surface modification layer is formed on the surface of the refined sulfide electrolyte. The surface modification layer can not only repair the surface damage of the sulfide electrolyte, but also has a high ionic conductivity, will not affect the ionic conductivity of the sulfide electrolyte, and can also avoid direct contact between the sulfide electrolyte and the positive electrode material, thereby reducing the space charge effect.
[0046] Please refer to Figure 1 As shown, the preparation method of the surface-modified sulfide electrolyte comprises the following steps:
[0047] S201, weigh 1.96 g TaCl5, 0.07 g ZrCl4, 0.04 g AlCl3, and 0.15 g LiOH, grind the above raw materials in proportion by ball milling at 700 rpm for 8 h to obtain a precursor;
[0048] S202, adding the above-obtained precursor to 25 g of refined sulfide electrolyte Li 5.5 PS 4.6 Cl 1.5 (D50 is 6 μm), and then the precursor is evenly dispersed on the surface of the sulfide electrolyte by ball milling at 150 rpm for 3 h to form a coating layer;
[0049] S203, the sulfide electrolyte with the coating layer is transferred to a box furnace, and sintered in an argon atmosphere at a temperature of 280°C for 3 hours, and then a surface modification layer with high ionic conductivity and high voltage resistance is formed on the surface of the refined sulfide electrolyte, that is, a sulfide electrolyte Li with a surface modification layer is obtained. 5.5 PS 4.6 Cl 1.5 @LiTa 0.9 Zr 0.05 Al 0.05O Cl 3.8 5.
[0050] Example 3
[0051] The present embodiment provides a surface-modified sulfide electrolyte, in which a surface modification layer is formed on the surface of the refined sulfide electrolyte. The surface modification layer can not only repair the surface damage of the sulfide electrolyte, but also has a high ionic conductivity, will not affect the ionic conductivity of the sulfide electrolyte, and can also avoid direct contact between the sulfide electrolyte and the positive electrode material, thereby reducing the space charge effect.
[0052] Please refer to Figure 1 As shown, the preparation method of the surface-modified sulfide electrolyte comprises the following steps:
[0053] S201, weigh 0.89 g TaCl5, 0.15 g ZrCl4, and 0.075 g LiOH, grind the above raw materials in proportion by ball milling at 750 rpm for 4 h to obtain a precursor;
[0054] S202, adding the above-obtained precursor to 10 g of refined sulfide electrolyte Li 5.4 PS 4.4 Cl 1.6 (D50 is 4 μm), and then the precursor is evenly dispersed on the surface of the sulfide electrolyte by ball milling at 120 rpm for 5 h to form a coating layer;
[0055] S203, then transferring the sulfide electrolyte with the coating layer to a box furnace, sintering it in a nitrogen atmosphere at a temperature of 300°C for 2 hours, and then forming a surface modification layer with high ionic conductivity and high voltage resistance on the surface of the refined sulfide electrolyte, that is, obtaining a sulfide electrolyte Li with a surface modification layer 5.4 PS 4.4 Cl 1.6 @LiTa 0.8 Z r0.2O Cl 3.8 .
[0056] Comparative Example 1:
[0057] 10 g of refined sulfide electrolyte Li6PS5Cl (D50 is 3 μm) was weighed and ball-milled at 100 rpm for 2 h. Then it was transferred to a tubular furnace and sintered in an argon atmosphere at a temperature of 120°C for 2 h to obtain an unmodified sulfide electrolyte.
[0058] Comparative Example 2:
[0059] Weigh 8 g of refined sulfide electrolyte Li 5.5 PS 4.6 Cl 1.5 (D50 is 6 μm), ball milled at 150 rpm for 3 h; then transferred to a box furnace and sintered in an argon atmosphere at a temperature of 280 ° C for 3 h to obtain an unmodified sulfide electrolyte.
[0060] Comparative Example 3:
[0061] Weigh 5 g of refined sulfide electrolyte Li 5.4 PS 4.4 Cl 1.6 (D50 is 4 μm), ball milled at 120 rpm for 5 h; then transferred to a box furnace and sintered in a nitrogen atmosphere at 300 ° C for 2 h to obtain an unmodified sulfide electrolyte.
[0062] Performance Testing
[0063] Metal lithium-based all-solid-state battery assembly and testing
[0064] For lithium metal-based batteries, the positive electrode active materials are LiCoO2, LiNi a Co b Tm c O2 (Tm=Mn or Al, a+b+c=1, a>0, b>0, c>0), xLiNi a Co b Mn c O2·(1-x)Li2MnO3(a+b+c=1, a>0, b>0, c>0, 0<x<1), LiNi 0.5 Mn 1.5 O4、LiMn x Fe 1-xPO4 (0<x<1) or more; the conductive agent is one or more of conductive carbon black, conductive graphite, carbon nanotube (CNT), carbon nanofiber (CNF), vapor grown carbon fiber (VGCF); the binder can be one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), nitrile rubber (NBR), styrene butadiene latex (SBR), carboxymethyl cellulose (CMC), polyvinyl alcohol, polyacrylate, polyimide, and polyamide. In the positive electrode film layer, the mass ratio of the positive electrode active material, the electrolyte material, the conductive agent, and the binder is (50~90): (1~50): (0.1~15): (0.1~15). The positive electrode active material is fully mixed with the surface-modified sulfide electrolyte prepared in the above Examples 1-3 or the unmodified sulfide electrolyte in Comparative Examples 1-3, a conductive agent (VGCF vapor-grown carbon fiber) and a binder (PTFE polytetrafluoroethylene) in a mass ratio of 80:20:2:0.6 to prepare a positive electrode film, and the positive electrode film is compounded with stainless steel to form a positive electrode sheet, that is, a positive electrode sheet is obtained;
[0065] Negative electrode: The negative electrode sheet includes a negative electrode material, which may be lithium-indium alloy, lithium metal, graphite (or other carbon-based materials), silicon (silicon-based materials), silicon-carbon negative electrode, and other negative electrode materials known in the art. The thickness of the negative electrode material layer in the negative electrode sheet is 20 μm to 100 μm.
[0066] Electrolyte: Sulfide electrolyte is used.
[0067] Battery assembly: The positive electrode and the negative electrode are placed on both sides of the electrolyte respectively to form a laminate consisting of the negative electrode-electrolyte-positive electrode. Stainless steel current collectors are arranged on both sides of the laminate, and leads are attached to the current collectors. The laminate is packaged in an aluminum-plastic bag and densified by applying a pressure of 50MPa using an isostatic pressing device to obtain a metal lithium-based all-solid-state battery.
[0068] The assembled all-solid-state battery was subjected to charge and discharge tests to evaluate the electrochemical performance of the battery. The test conditions were:
[0069] First charge and discharge test: The solid-state battery is charged and discharged at 0.1C constant current for 1 cycle at 25°C, with a voltage range of 2.7-4.5V.
[0070] AC impedance test: After the solid-state battery is charged and discharged for the first time at 25°C, the test frequency is 100kHz-0.01Hz and the amplitude is 10mV.
[0071] Long cycle test: The solid-state battery is charged and discharged for 100 cycles at 0.1C constant current at 25°C, with a voltage range of 2.7-4.5V.
[0072] The test results are shown in Table 1.
[0073] Table 1 is the performance test results of the embodiments and comparative examples
[0074]
[0075] From Table 1, Appendix Figure 2 and attached Figure 3 The test results show that:
[0076] like Figure 2 As shown, compared with Example 1 and Comparative Example 1, the sulfide electrolyte Li6PS5Cl@LiNb 0.6 Zr 0.4 OCl 3.6 By using CuK α,1 In the spectrum measured by an X-ray diffraction device (XRD) with rays, there are diffraction peaks at 2θ=14°±0.5° and 24.5°±0.5°; the X-ray energy dispersive spectrometer (EDS) can detect that the sulfide electrolyte in Example 1 has lithium, oxygen, halogen, and M elements on the surface.
[0077] like Figure 3 As shown in the electrochemical impedance spectroscopy (EIS) diagrams of Example 2 and Comparative Example 2, it can be seen that the impedance value of Comparative Example 2 is greater than that of Example 2. According to the formula of ionic conductivity It can be seen that when the thickness and area are the same, the ionic conductivity of Example 2 is higher than that of Comparative Example 2, where σ represents the impedance value, L represents the thickness, S represents the area, and R represents the impedance value. 5.5 PS 4.6 Cl 1.5 @LiTa 0.9 Zr 0.05 Al 0.05O Cl 3.8 The ionic conductivity of 5 is significantly higher than that of the sulfide electrolyte Li in Comparative Example 2. 5.5 PS 4.6 Cl 1.5 .
[0078] Compared with Example 3 and Comparative Example 3, the all-solid-state battery assembled with the sulfide electrolyte obtained in Example 3 is significantly improved in terms of the first discharge specific capacity and cycle performance under high voltage. The surface modification layer of the sulfide electrolyte effectively avoids the decomposition of the sulfide electrolyte under high voltage, reduces the interfacial impedance, is beneficial to the battery capacity, and improves the comprehensive electrochemical performance of the all-solid-state battery.
[0079] In summary, the present application uses a precursor obtained from an oxygen-containing lithium compound and a halogen-containing compound to repair the surface of a refined sulfide electrolyte, and reacts on the surface of the sulfide electrolyte to generate a surface modification layer with high ionic conductivity and high voltage resistance. The surface modification layer will not affect the ion transport of the sulfide electrolyte, and can also inhibit the side reaction of the sulfide electrolyte with the positive electrode active material under high voltage, thereby reducing the interface impedance. At the same time, the oxygen-containing lithium compound and the halogen-containing compound are used as coating materials, and the lithium element is used as a lithium supplement, which can improve the comprehensive electrochemical performance of the all-solid-state battery.
[0080] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0081] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A surface-modified sulfide electrolyte, characterized in that: include: A sulfide electrolyte and a surface modification layer, wherein the surface modification layer is formed on the surface of the sulfide electrolyte, and the surface modification layer includes a compound; The chemical formula of the compound is Li M a OX b , wherein 0≤a≤1, 2≤b≤4, and X is one or more of Cl, Br, and F; wherein M is one or more of Al, Nb, Ta, and Zr.
2. The surface-modified sulfide electrolyte according to claim 1, characterized in that The material of the surface modification layer has diffraction peaks at 2θ=14°±0.5° and 24.5°±0.5° in the X-ray diffraction spectrum.
3. The surface-modified sulfide electrolyte according to claim 1, characterized in that The chemical formula of the sulfide electrolyte is Li 7-a PS 6-a X a , wherein X is one or more of F, Cl, Br, I, 0≤a≤2, and ionic conductivity>2.0mS / cm.
4. The surface-modified sulfide electrolyte according to claim 3, characterized in that The particle size D50 of the sulfide electrolyte is ≤8 μm.
5. A method for preparing a surface-modified sulfide electrolyte as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Mixing an oxygen-containing lithium compound and a halogen-containing compound to obtain a precursor; Adding the precursor into the sulfide electrolyte and mixing them, so that the oxygen-containing lithium compound and the halogen-containing compound are uniformly dispersed on the surface of the sulfide electrolyte to form a coating layer; The sulfide electrolyte with the coating layer is subjected to low temperature annealing treatment to obtain a sulfide electrolyte with a surface modification layer.
6. The preparation method according to claim 5, characterized in that: The total mass of the oxygen-containing lithium compound and the halogen-containing compound is 0.1-10% of the sulfide electrolyte.
7. The preparation method according to claim 5, characterized in that: The halogen-containing compound is one or more of NbF5, TaF5, ZrF4, AlF3, NbCl5, TaCl5, ZrCl4, AlCl3, NbBr5, TaBr5, ZrBr4, AlBr3, NbI5, TaI5, ZrI4, and AlI3; The oxygen-containing lithium compound is one or more of Li2CO3, Li2O and LiOH.
8. The preparation method according to claim 5, characterized in that: The oxygen-containing lithium compound and the halogen-containing compound are mixed by grinding; And / or, the grinding method is ball milling, the rotation speed of the ball milling is 100-800 rpm, and the ball milling time is 1-40 hours.
9. The preparation method according to claim 5, characterized in that: The annealing temperature is 70-350° C., and the annealing time is 1-8 hours.
10. An all-solid-state battery, characterized in that: It comprises a positive electrode layer, a negative electrode layer and an electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer is a composite positive electrode, and the electrolyte used for the composite positive electrode is a surface-modified sulfide electrolyte as described in any one of claims 1 to 4 or a surface-modified sulfide electrolyte obtained by the preparation method as described in any one of claims 5 to 9.